Effect of leaching reagent on leaching process of europium, terbium and yttrium from liquid crystal display - Farouq, Ahmat (2019)
Liquid crystal display (LCD) monitor uses color filter to produce color gamut and this particular filter is mainly made up from europium (Eu), terbium (Tb) and yttrium (Y) of Rare Earth Elements (REEs). Recycling as well as recovering of all these elements are of particularly important due to the scarcity of REEs and also the abundance capacity of electronic waste (e-waste), especially LCD monitors that available worldwide. In this regard, one of the crucial steps in recovering activities is involving leaching process. Thus, the dissolution behavior of the elements in the aqueous solution needs to be critically understood in order to determine the priority sequence of the REEs that to be extracted from the LCD scraps. This study focuses on the dissolution process of Eu, Tb, and Y using hydrochloric (HCl), sulfuric (H2SO4) and nitric (HNO3) acids respectively, whereby it is generally divided into two main parts. The first part relates to the thermodynamic property analysis, whereby Pourbaix diagram has been utilized as the tool in mainly representing the dissolution stability. The results showed that Eu, Tb, and Y are dissolved in HCl, H2SO4 and HNO3 acids respectively as an individual cations and forming complex with ligand and other radical. Meanwhile, the second phase of the study deals with assessing the dissolution effectiveness via analytical testing, particularly based on two experimental modes – single and two stages of dissolution processes. Regarding this, the amount of Eu, Tb, and Y were measured respectively using XRF and ICP-MS techniques. Unfortunately, the XRF method was unable to detect any of the elements due to their very small REEs concentration relative to other compositions. However, the results of ICP-MS analysis have shown that only Y element was dissolvable feasibly either by single or two-stage steps. This observation also suggests that the other two elements, which consist of Eu and Tb, are extremely low in quantity and complicated to be recovered. In addition, both HNO3 and H2SO4 solutions were identified as the best option to be utilized as the dissolution reagents relative to HCl. The morphology structure analysis on the remaining samples particularly after the dissolution completed indicates that the morphology of H2SO4-HNO3 as well as HNO3-H2SO4 samples are relatively richer in the molecules compactness. This is perhaps due to the silicon elements that did not dissolve effectively during the dissolution process. It can be summarized that only Y element is practically feasible to be extracted rather than Eu or Tb from the LCD e-waste.